2019
DOI: 10.1200/jco.18.01480
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of MicroRNA-371a-3p (M371 Test) as a New Biomarker of Testicular Germ Cell Tumors: Results of a Prospective Multicentric Study

Abstract: PURPOSE Previous studies suggested that serum levels of microRNA (miR)-371a-3p (so-called M371 test) have a much higher sensitivity and specificity than the classic markers of testicular germ cell tumors (GCTs) and are applicable toward both seminoma and nonseminoma. We sought to confirm the usefulness of this test as a novel biomarker for GCT. PATIENTS AND METHODS In a prospective, multicentric study, serum samples of 616 patients with testicular GCTs and 258 male controls were examined for serum levels of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
280
9
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 270 publications
(321 citation statements)
references
References 41 publications
21
280
9
11
Order By: Relevance
“…As in advanced clinical stages the marker substance is released from both the primary tumor and metastatic seeds it is rational that the correlation of tissue expression with serum levels is only significant in cases confined to the testis. The serum level of circulating miR-371a-3p is obviously a product of the number of miR-producing tumor cells (tumor bulk) as shown previously [5] and of the specific secreting capacity of the individual GCT as shown herein. Most probably, additional biological determinants e. g. direct vascular invasion of the tumor and other hitherto unknown factors do also affect the serum level of miR-371a-3p.…”
Section: Correlation Of Mir-expression Levels In Tissue With Serum Lesupporting
confidence: 72%
See 4 more Smart Citations
“…As in advanced clinical stages the marker substance is released from both the primary tumor and metastatic seeds it is rational that the correlation of tissue expression with serum levels is only significant in cases confined to the testis. The serum level of circulating miR-371a-3p is obviously a product of the number of miR-producing tumor cells (tumor bulk) as shown previously [5] and of the specific secreting capacity of the individual GCT as shown herein. Most probably, additional biological determinants e. g. direct vascular invasion of the tumor and other hitherto unknown factors do also affect the serum level of miR-371a-3p.…”
Section: Correlation Of Mir-expression Levels In Tissue With Serum Lesupporting
confidence: 72%
“…Of note, all subtypes of GCT except teratoma stained positive for the miR-371a-3p probe. The absence of miR-371a-p staining in teratoma cells is consistent with the non-expression of this miR in serum of GCT patients [4,5,16]. Likewise, in an evaluation of miR-371a-3p expression levels in GCT subtypes by RNA extraction from formalin fixed paraffin embedded orchiectomy specimens, Vilela-Salgueiro et al revealed a strong expression in all GCT subtypes except teratoma [25].…”
Section: Intracellular Localization Of Mir-371a-3p By Ishsupporting
confidence: 54%
See 3 more Smart Citations